Anti-inflammatory Effect of Ethyl Acetate Fraction of Ethanol Extract of Guazuma ulmifolia Lamk - Emsutrisna, E; Wahyuni, Sri; Sujono, Tanti Azizah; Maryati, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The aim of this research is to investigate the anti-inflammatory effect of ethyl acetate fraction of ethanol extract of Guazuma ulmifolia Lamk. The research used pre and post test with control group design. A number 25 white rats wistar strain were devided into 5 groups. Group 1 was treated by Diclofenac sodium at dose of 50mg/kgbw; group 2 was treated by Aqueous 2 mL/rats; group 3, 4 and 5 were treated by ethyl acetate fraction of ethanol extract of Guazuma ulmifolia Lamk. (EAGU) at dosage of 250; 500 and 1000 mg/kgbw respectively. After treated, volume of rats’s right paw was measured by plethysmometer for 330minutes. The compound of ethyl acetate fraction of ethanol extract of Guazuma ulmifolia Lamk was analyzed by phytochemicals analysis. The EAGU at dosage of 1000 mg/kgbw can reduce edema volume at minutes 60 and minutes 90 significantly (by anova P. <0.05). The phytochemical compounds of EAGU are alkaloid, flavonoid, tannin, saponin and triterpen.